Study on the Impact of Diaphragm Deformation on Fatigue Performance and Maintenance Strategies in Steel Bridge Decks - Chuanxi Li; Yue Yao; Zhendong Li; Bohai Ji (Applied Sciences)
Localized diaphragm (transversal plate) deformation and buckling were identified at the arc notch region during structural inspections of an operational steel bridge. To evaluate the potential structural consequences, alterations in the fatigue performance and stress characteristics induced by this deformation were systematically investigated through in situ monitoring combined with numerical simulation. It was demonstrated that the global load-transfer mechanism of the orthotropic steel deck (OSD) system remained minimally compromised. While within the localized deformation zone, the stress magnitudes at the diaphragm-to-U-rib (DU) welds were observed to be significantly amplified, and the stress concentration zones were found to be relocated to geometrically depressed regions. Based on the deformation-stage mechanical responses, the strategic employment of residual compressive stress generated through controlled hammer peening was proposed for counteracting stress escalation at DU welds recently caused by diaphragm buckling, whereas steel plate reinforcement strategies were recommended for mitigating progressive deformation development.